The Auction Status of East Asian Artworks in Modern America - Ma, Yingling (Journal of Literature and Arts Research, 2025)
This paper examines the evolution of auction activities related to East Asian artworks in the United States from the mid-to-late 1930s, with a particular focus on the transformation of auction catalogs from simple listings to systematic classifications. By analyzing auction catalogs from 1890 to 1940, this study explores the market dynamics and status of Chinese ceramics—particularly Song dynasty ceramics—Japanese ukiyo-e, and Korean Goryeo celadon. Notably, the increased recognition of Goryeo celadon in the American market, influenced by Japanese procurement activities in 1909, reflects shifts in market demand and collecting trends. This article argues that the development of auction catalogs not only responded to collectors’ preferences but also played a crucial role in shaping American perceptions of East Asian artworks. Furthermore, antique dealers were instrumental in this process, serving as intermediaries between collectors and the evolving market landscape.